laser versus conventional acid etching technique on bond strength of orthodontic brackets (An in vitro stydy) - Khidhair A Al-Jumaili; Abdul- Rahman I Ali; Zaid A Ibrahim (University of Mosul, College of Dentistry, 2011)
Aims: This in vitro study was undertaken to evaluate and compare the effect of acid etching and/or diode laser (1064 nm) irradiation on shear bond strength of orthodontic brackets. Materials and Methods: Thirty freshly extracted human premolars were included in this study. Laser irradiation was done by using the new 1064 nm diode laser with output power of 2.5 Watt in continues mode, also use stainless steel orthodontic brackets (Roth, 22-slot size), and use orthodontic flowable composite resin which needs no bonding fluid. The 30 human teeth were divided into 3 groups (each group consist of 10 teeth): Group A-use acid etching (37% phosphoric acid) for 1 minute to bond bracket to tooth surface (control group), group B-use laser irradiation for 30 seconds with Indian ink (coated on teeth). Group C-use laser irradiation for 30 seconds with Indian ink after that use acid etching for 1 minute. Shear bond strength measured by using unconfined shear testing machine at a cross head speed of 5 mm/min. Results: The shear bond strength means were as follows: Group A: 11.27 MPa, group B: 6.21 MPa, group C: 14.04 MPa. The acid etching after 1064 nm diode laser irradiation (group C) has significantly higher bond strength (p ˂ 0.05) than remaining groups. In group B, orthodontic brackets had significantly lower shear bond strength (p ˂ 0.05) than remaining groups. Conclusions: These results indicate that acid etching after laser irradiation enhances and improves the bonding of orthodontic composite resin to human enamel. In the same time 1064 nm diode laser irradiation with ink coating is not consider as a replacement to acid etching in bonding of orthodontic brackets to human enamel